GAGASAN STRATEGIS POROS MARITIM BAGI INDONESIA - Bambang Sugeng Irianto (Universitas Muhammadiyah Gresik, 2019)
In creating the Maritime Axis there must be a division of the maritime zone to reinforce the territorial waters of Indonesia which manifest through clear restrictions accompanied by clear and explicit rules regarding inland waters, archipelagic waters, territorial sea and additional zones. Given that Indonesia is a coastal country, Indonesia has the authority to prevent violations of customs, fiscal, immigration or sanitary legislation within its territorial sea area. This oversight can be complemented by eradication measures and the coastal state can punish violators of legislation